DNA index as a strong prognostic factor in patients with adenocarcinoma of the pancreatic head: results of a 5-year prospective study - Kamphues, Carsten; Al-Abadi, Hussein; Stenzinger, Albrecht (Pancreas, 2013)
Objectives To improve the devastating prognosis of pancreatic cancer; the identification of reliable predictive factors is crucial. The aim of the present study was to prospectively assess the prognostic value of DNA index determined by image cytometry as an predictive factor in pancreatic head cancer. Methods The DNA ploidy and the DNA index of 61 patients were evaluated by DNA image cytometry and were found to be correlated, as well as standard histopathologic parameters, with patient survival. Results Through the DNA image cytometry, 15 tumors (24.6%) were identified as diploid and 46 (75.6%) as nondiploid. The median DNA index in the entire cohort was 1.9 (range, 1.0-2.5). Tumor stage, lymph node status, lymph node index, lymphatic invasion, and DNA index were identified as prognostic factors in the univariate analysis, but only DNA index (hazard ratio, 3.137; 95% confidence interval, 1.149-8.566; P = 0.026) and lymph node status (hazard ratio, 0.377; 95% confidence interval, 0.186-0.765; P = 0.007) were identified as independent predictive factors in the multivariate analysis. Conclusions The DNA index represents an independent predictive marker in patients with pancreatic head cancer and a potential tool in designing specific treatment strategies for patients with pancreatic cancer.